The Influence of Organizational Culture, Organizational Learning and Employee Competency on Employee Performance PT. Bank Mandiri (Persero), Tbk. Area Palembang Arief - Muhammad Rafliansyah Nizar; Yos Karimudin; Agustina Hanafi; Zunaidah; Afriyadi Cahyadi (International Journal of Economics Accounting and Management, 2025)
This study was conducted to examine the extent to which organizational culture, organizational learning, and employee competence influence employee performance at PT Bank Mandiri (Persero) Tbk., Palembang Arief Area. A total sample of 100 employees was selected to represent the population, with data collection carried out using both primary and secondary sources. Primary data were obtained through structured questionnaires, while secondary data were drawn from relevant organizational documents and records. To analyze the relationships among the variables, multiple linear regression was applied as the primary analytical technique. The results of the study demonstrate that organizational culture has a significant effect on employee performance, organizational learning also exerts a significant influence, and employee competence likewise contributes significantly to improving performance outcomes. These findings collectively highlight the importance of fostering a strong organizational culture, supporting continuous learning initiatives, and enhancing employee competence in order to optimize overall performance within the organization